2015
DOI: 10.1080/14786419.2015.1060592
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, cytotoxicity, antimicrobial and antifungal activity of several essential oils

Abstract: Essential oils (EOs) are known and used for their biological, antibacterial, antifungal and antioxidant properties. Numerous studies have shown that EOs exhibit a large spectrum of biological activities in vitro. The incidence of drug-resistant pathogens and the toxicity of antibiotics have drawn attention to the antimicrobial activity of natural products, encouraging the development of alternative treatments. The aim of this study was to analyse the phytochemical and the cytotoxic characteristic of 36 EOs; we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…MS detection was performed with electron ionization (EI) at 70 eV, operating in the full-scan acquisition mode in the m/z range 40–400. EOs were diluted 1:20 ( v /v) with n -hexane before GC-MS analysis [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MS detection was performed with electron ionization (EI) at 70 eV, operating in the full-scan acquisition mode in the m/z range 40–400. EOs were diluted 1:20 ( v /v) with n -hexane before GC-MS analysis [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…The injector and detector temperatures were set at 250 °C and 300 °C, respectively. EOs and reference standards were diluted 1:20 ( v /v) with n -hexane before GC-FID analysis [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. tropicalis and C. parapsilosis were more sensitive to the L. littoralis oil compared to the other Candida species tested, and C. parapsilosis was more sensitive to the P. trimera oil compared to the other Candida species in the present study. Given the experimental data obtained in this case and our previous works [30,31], the resistance may vary depending on the species of Candida and the essential oils. The current work indicated that L. littoralis oil was effective against C. tropicalis and C. parapsilosis with MIC and MLC of 2% (v/v), while exerting no cytotoxicity at the same concentration.…”
Section: Discussionmentioning
confidence: 57%
“…Two mechanisms of cytotoxic activity have been hypothesized: 1) lipophilic hydrocarbons contained in EOs may accumulate in the lipid layer and distort the lipid-protein interaction; 2) other types of interactions excluding lipid component may occur in the proximity of protein hydrophobic portions, resulting in their destabilization [15]. Among non-phenolic EOs compounds, alkyl substituents (alkenyl groups rather than alkyls) have been reported to influence cytotoxic activity [16]. The present study is in agreement with the above mentioned considerations regarding the activity and efficacy of cytotoxic mechanisms through which EOs act on human cells.…”
Section: Discussionmentioning
confidence: 99%